2024
DOI: 10.1186/s12916-024-03266-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of virtual reality for pain relief in medical procedures: a systematic review and meta-analysis

Jhia J. Teh,
Dominic J. Pascoe,
Safiya Hafeji
et al.

Abstract: Background Effective pain control is crucial to optimise the success of medical procedures. Immersive virtual reality (VR) technology could offer an effective non-invasive, non-pharmacological option to distract patients and reduce their experience of pain. We aimed to evaluate the efficacy of Immersive virtual reality (VR) technology in reducing patient’s pain perception during various medical procedures by conducting a systematic review and meta-analysis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 176 publications
0
0
0
Order By: Relevance
“…During VR distraction, functional brain imaging studies have revealed decreased activity in pain perception areas and increased activity in cortical areas linked to attention and pain modulation. minimizes drug use, accelerates postoperative recovery, enhances patient experience 20 .…”
Section: Alternatives To Conventional Local Anesthetic Techniques Ava...mentioning
confidence: 99%
“…During VR distraction, functional brain imaging studies have revealed decreased activity in pain perception areas and increased activity in cortical areas linked to attention and pain modulation. minimizes drug use, accelerates postoperative recovery, enhances patient experience 20 .…”
Section: Alternatives To Conventional Local Anesthetic Techniques Ava...mentioning
confidence: 99%